If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(8x + -5) = 35 + 9x Reorder the terms: -2(-5 + 8x) = 35 + 9x (-5 * -2 + 8x * -2) = 35 + 9x (10 + -16x) = 35 + 9x Solving 10 + -16x = 35 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 10 + -16x + -9x = 35 + 9x + -9x Combine like terms: -16x + -9x = -25x 10 + -25x = 35 + 9x + -9x Combine like terms: 9x + -9x = 0 10 + -25x = 35 + 0 10 + -25x = 35 Add '-10' to each side of the equation. 10 + -10 + -25x = 35 + -10 Combine like terms: 10 + -10 = 0 0 + -25x = 35 + -10 -25x = 35 + -10 Combine like terms: 35 + -10 = 25 -25x = 25 Divide each side by '-25'. x = -1 Simplifying x = -1
| 6+3x=5x-10x+10 | | Ak-r=oj | | 6963.7=83.9a | | 6.5-8.1=9.75-5.4x | | 6+3x=5x+10x+10 | | 7(1-6x)=-29-6x | | -4.1x+7.2=17.7 | | 2(2.55+15x)=50.10 | | 17(2x+1)=x-3x-3 | | 4x=7y-12 | | 7a^3-35a^2-42a=0 | | (4b+6)(b-4)= | | (9b-6)-2(4b+3)=-7 | | 3t+15=4t-7 | | 3-4a=5(a+3) | | 5x+6=12x-24 | | 4(-7n-6)=108 | | -73+8x=-3x+59 | | 180=11x+8+8x+1 | | (a-5)(2a-6)= | | 4n+=6n+7 | | 8x-(5x+9)=3x-5x-(x+3) | | 37n+16=2-18n | | (6t+4)(6t-4)=0 | | -9+3x+4x-6=-4 | | -2y-33+8=8-5y-12 | | 8n+-13=13+-8n | | 2.55+15x=50.10 | | 2+5x=7+2x | | 3+7n+10=3n | | 90+0.40m=30+0.90m | | -93=-3(-7x+3) |